2013
DOI: 10.1080/0163853x.2013.824286
|View full text |Cite
|
Sign up to set email alerts
|

Gestural Viewpoint Signals Referent Accessibility

Abstract: Gestural viewpoint signals referent accessibility AbstractThe tracking of entities in discourse is known to be a bimodal phenomenon. Speakers achieve cohesion in speech by alternating between full lexical forms, pronouns, zero anaphora as they track referents. They also track referents in co--speech gestures. In this study, we explored how viewpoint is deployed in reference tracking focusing on representations of animate entities in German narrative discourse. We found that gestural viewpoint systematically va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 33 publications
(63 reference statements)
3
40
1
Order By: Relevance
“…Speakers point to the entities they refer to with speech, use iconic gestures as they move the fingers of an inverted V-hand in a wiggling manner while saying 'he walked across', use bodily demonstrations of reported actions as they tell narratives, convey different viewpoints of events or use gesture spaces indexing different levels of discourse cohesion parallel to marking similar discourse devices found in speech (e.g. [10,11]). Thus, there has been mounting evidence at the production level that cospeech gestures contribute semantic, syntactic, discursive and pragmatic information to the verbal part of an utterance, forming composite utterances with semiotic diversity [6][7][8]12].…”
Section: Introductionmentioning
confidence: 99%
“…Speakers point to the entities they refer to with speech, use iconic gestures as they move the fingers of an inverted V-hand in a wiggling manner while saying 'he walked across', use bodily demonstrations of reported actions as they tell narratives, convey different viewpoints of events or use gesture spaces indexing different levels of discourse cohesion parallel to marking similar discourse devices found in speech (e.g. [10,11]). Thus, there has been mounting evidence at the production level that cospeech gestures contribute semantic, syntactic, discursive and pragmatic information to the verbal part of an utterance, forming composite utterances with semiotic diversity [6][7][8]12].…”
Section: Introductionmentioning
confidence: 99%
“…Empirical studies on reference tacking in various languages seem to support this account. For example, Debreslioska et al (2013) found that German adult native speakers use mainly nominal forms with less accessible referents while they prefer attenuated form with more accessible referents. In the following section we provide a short overview of linguistic forms available in Turkish and previous literature on reference tracking in speech in Turkish.…”
Section: Reference Tracking In Speechmentioning
confidence: 98%
“…That is they use the visual modality to maintain discourse cohesion, i.e., to mark the accessibility of the referents in discourse (Debreslioska, Özyürek, Gullberg, & Perniss, 2013;Gullberg, 2006;Perniss & Özyürek, 2015;Yoshioko, 2008). Studies suggest that similar to speech, co-speech gestures, the meaningful movements of the hands that accompany speech, are sensitive to referential context in terms of the quantity of marking material (Gullberg, 2003(Gullberg, , 2006Levy & Fowler 2000;McNeill & Levy, 1993).…”
Section: Introductionmentioning
confidence: 98%
“…It is important to note, however, that because the criterion for categorizing a gestures as having an observer viewpoint is that a referent is represented as a whole on the forelimbs (e.g., McNeill, 1992McNeill, , 2005Parrill, 2009;Debreslioska et al, 2013), the difference between character and observer viewpoint in these studies essentially boils down to what happens on the hands.…”
Section: Describing Gestur Al Elementsmentioning
confidence: 99%
“…In Figure 1a, the speaker shows how a character in her narrative acts by using her own body as Figure 1b the speaker uses only her right hand to show the actions of a character, that is, she uses her hand to show the entity as a whole. In the gesture literature, this difference has generally been referred to as a difference in viewpoint (McNeill, 1992(McNeill, , 2005Beattie & Shovelton, 2001Parrill, 2009, 2010: Stec, 2012Debreslioska, Özyürek, Gullberg, & Perniss, 2013) -most often framed as c h a r a c t e r v i e w p o i n t versus o b s e r v e r v i e w p o i n t, although studies sometimes use different labels for comparable distinctions. 2 Although the term viewpoint is often used in the co-speech gesture literature, exactly what constitutes a viewpoint is rarely specified.…”
Section: Viewpoint In Gesturementioning
confidence: 99%